Experiences of BA Sociology Students from a Philippine State University: Recruitment, Retention, and Future Aspirations - Quintos, Mark Anthony; Iwayama, Minami (Social Sciences and Development Review, 2025)
Sociology as an undergraduate program in the Philippines has expanded significantly. A total of 49 higher educational institutions offer an undergraduate degree in Sociology; 20 of which are in Luzon and 8 are in Metro Manila. Despite this growth, Sociology departments face challenges in recruiting and retaining students amidst a competitive academic landscape. This study was conducted with students from a Philippine state university, exploring their motivations for enrolling, reasons for staying, perceived strengths and weaknesses of the program, and their post-graduation plans. The insights gained from this research could guide future improvements to Sociology programs to better meet the needs and aspirations of students.
Keywords: Sociology; Education; Philippines; Law School; University